Uneven geographies of COVID-19: reviewing geographical research agendas and concepts from a syndemics perspective - Butsch, Carsten; Everts, Jonathan; Bork-Hüffer, Tabea (Geography compass, 2024)
Building upon a review of geographic research agendas and concepts related to the uneven geographies of COVID-19, this first of three articles debates the benefits of geographic analyses to the syndemic approach and, vice versa, of a syndemics perspective to geographic analyses. The syndemics perspective was proposed by critical medical anthropologists. It seeks to deepen the understanding of the structural dimensions and processes that lead to the convergence and cascading of multiple epidemics in specific population groups. Geographers have also highlighted the intersections of multiple health or other crises during COVID-19, when the pandemic and global health emergency coincided with and escalated existing structural inequalities produced by the climate crisis, environmental degradation, political conflicts and war, socio-economic disparities and poverty, social divisions, racism, hatred and violence, mental health problems and stress. Geographers have mobilized concepts such as scale, territory, borders and intersectionality to unravel the uneven unfolding and consequences of the global health emergency for diverse population groups. We therefore argue that geography has a lot to contribute to the understanding of the spatial and contextual dimensions of COVID-19 as a pandemic as well as a syndemic – but it has so far not actively employed the latter concept's analytical lens. Mobilizing the syndemics approach can contribute to more comprehensive accounts of the structural dimensions and processes that continue and cascade in pandemics.